Reactions of bereaved spouses to spousal death in Nigeria: implications for mental health counselling - Muhammed, Shuaib Abolakale (Penerbit Universiti Kebangsaan Malaysia, 2023)
Death of spouse is one of the most traumatic life events which engender different reactions. This study examined grief reactions of bereaved spouses in Nigeria. A quantitative descriptive survey method was used in selecting a sample of 1,594 bereaved spouses across the six geo political zones in Nigeria through purposive and proportional sampling techniques. Grief Reactions of Bereaved Spouses Scale was the major instrument used to amass data. The instrument was validated by experts and the reliability measure was ascertained. The correlation coefficient result obtained was 0.87. Means, percentages, rank order, t-test, and Analysis of Variance statistical measures were employed to analyze the data collected for the study. The findings of the study revealed that 53.5% of the respondents had positive grief reactions while 46.5% had negative reaction; the common grief reactions of respondents include loneliness, sleeplessness and depressive moods among others. The number of years that had passed since the loss had an impact on grieving people in Nigeria, but gender and nature of death had no bearing on how they were feeling. The suggestion is that grieving spouses need support to manage their emotions. Counselors ought to offer appropriate community-based intervention programs to help bereaved spouses of all ages, years of loss, types of deaths and genders deal with their sorrow.